1, 4 Butanesultone Functionalized Graphitic Carbon Nitride: Efficient Catalysts for the One-Pot Synthesis of 1, 4-Dihydropyridine and Polyhydroquinoline Derivative through Hantzsch Reaction. (3rd July 2022) - Rahmati, Monavar; Ghafuri, Hossein; Ghanbari, Nastaran; Tajik, Zeinab
Abstract: In this research, covalently linked sulfonic acid (SO3 H) modified g-C3 N4 nanosheet (CNNs) catalysts was prepared. For this purpose, graphitic carbon nitride nanosheets (CNNs) were successfully synthesized. By the reaction of synthesized CNNs with 1, 4-butane-sultone, CNNs-Bu-SO3 H organocatalyst was produced. The synthesized organocatalyst was characterized by FTIR, EDS, XRD, FESEM, and TGA analysis. The catalytic efficiency of the CNNs-Bu–SO3 H was explored for the synthesis of 1, 4-dihydropyridine and polyhydroquinoline derivatives. The synthesized organocatalyst exhibits good thermal stability, high acidity and could be used up to five reaction cycles without a noticeable decrease in catalytic activity.